2015
DOI: 10.2169/internalmedicine.54.3500
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Effusion and Multiple Organ Involvement Are Independent Predictors of Mortality in Patients with Systemic Light Chain Amyloidosis

Abstract: Objective Left ventricular (LV) functions assessed by echocardiography and cardiac biomarkers are strong predictors of mortality in patients with systemic light chain (AL) amyloidosis. However, most previous studies have been conducted in Western countries, and the predictors of mortality in Asian patients with AL amyloidosis have not been characterized. To address this issue, we aimed to determine the predictors of mortality in Asian patients with biopsy-confirmed AL amyloidosis. Methods We retrospectively en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…It is, therefore, suggested in the current guidelines as a standard assessment in the evaluation of patients with HF and should, therefore, also be part of a detailed echocardiographic examination in patients with CA [ 7 ]. One study reported on the predictive effect of pericardial effusion in patients with light chain amyloidosis (AL); however, the studied cohort was small ( n = 31) and only analysed the effects of effusion on all-cause death rather than cardiac death [ 8 , 9 ]. There has recently been evidence that pericardial effusion may also be a sign of myocardial edema following local amyloid infiltration and consecutive inflammation in patients with AL and ATTR [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, suggested in the current guidelines as a standard assessment in the evaluation of patients with HF and should, therefore, also be part of a detailed echocardiographic examination in patients with CA [ 7 ]. One study reported on the predictive effect of pericardial effusion in patients with light chain amyloidosis (AL); however, the studied cohort was small ( n = 31) and only analysed the effects of effusion on all-cause death rather than cardiac death [ 8 , 9 ]. There has recently been evidence that pericardial effusion may also be a sign of myocardial edema following local amyloid infiltration and consecutive inflammation in patients with AL and ATTR [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of confirmed plasma cell dyscrasia, immunohistochemical techniques are the most useful for classifying the type of amyloidosis [ 8 ]. Several studies concluded that cardiac involvement in amyloidosis is the major determinant of mortality in patients with AL amyloidosis, and the prognosis is very poor [ 9 11 ]. However, Quevedo et al [ 12 ] insisted that early diagnosis and prompt therapy are crucial to the reversal of AL-related cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, pericardial effusions are small and not hemodynamically relevant. There are divergent data on the prognostic significance of pericardial effusions in patients with CA [27]. Pleural effusion: In approximately 40% of patients with AL, pleural effusions are present.…”
Section: Echocardiographymentioning
confidence: 99%